MicroRNAs in colorectal cancer: Role in metastasis and clinical perspectives - Muhammad, Shan (World J Gastroenterol, 2014)
Colorectal cancer (CRC) is the third most common malignancy and the third leading cause of cancer related deaths in the United States. Almost 90% of the patients diagnosed with CRC die due to metastases. MicroRNAs (miRNAs) are evolutionarily conserved molecules that modulate the expression of their target genes post-transcriptionally, and they may participate in various physiological and pathological processes including CRC metastasis by influencing various factors in the human body. Recently, the role miRNAs play throughout the CRC metastatic cascade has gain attention. Many studies have been published to link them with CRC metastasis. In this review, we will briefly discuss metastatic steps in the light of miRNAs, along with their target genes. We will discuss how the aberration in the expression of miRNAs leads to the formation of CRC by effecting the regulation of their target genes. As miRNAs are being exploited for diagnosis, prognosis, and monitoring of cancer and other diseases, their high tissue specificity and critical role in oncogenesis make them new biomarkers for the diagnosis and classification of cancer as well as for predicting patients’ outcome. MiRNA signatures have been identified for many human tumors including CRC, and miRNA-based therapies to treat cancer have been emphasized lately. These will also be discussed in this review.